2017
DOI: 10.1002/mbo3.486
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Escherichia coli for production of 2‐Phenylethylacetate from L‐phenylalanine

Abstract: In order to meet the need of consumer preferences for natural flavor compounds, microbial synthesis method has become a very attractive alternative to the chemical production. The 2‐phenylethanol (2‐PE) and its ester 2‐phenylethylacetate (2‐PEAc) are two extremely important flavor compounds with a rose‐like odor. In recent years, Escherichia coli and yeast have been metabolically engineered to produce 2‐PE. However, a metabolic engineering approach for 2‐PEAc production is rare. Here, we designed and expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…268 mg/L from phenylalanine feeding Combined the synthesis pathway of 2-phenylethanol from phenylalanine and ester formation using alcohol transferase ATF1 (Guo et al, 2017).…”
Section: Mg1655mentioning
confidence: 99%
“…268 mg/L from phenylalanine feeding Combined the synthesis pathway of 2-phenylethanol from phenylalanine and ester formation using alcohol transferase ATF1 (Guo et al, 2017).…”
Section: Mg1655mentioning
confidence: 99%
“…Another interesting bioproduct produced by SSF are aroma compounds. One of the most used aroma compounds are roselike scented 2-phenethyl alcohol (2-PE) (Stark et al, 2003) and the floral fragrance 2-phenethyl acetate (2-PEA) (Guo et al, 2017). Martinez-Ávila et al (2017Martinez-Ávila et al ( , 2018 reported a residuebased productive process to obtain fruit-like aromas using Kluyveromyces marxianus and sugarcane bagasse via SSF.…”
Section: Product Developmentmentioning
confidence: 99%
“…One of the most relevant flavor-alcohols is the 2-PE, an aromatic alcohol with a delicate fragrance of rose petals (Burdock 2010) widely applied in diverse types of products, such as perfumes, cosmetics, pharmaceuticals, foods, and beverages (Carlquist et al 2015). Furthermore, 2-PE can be used as raw material to produce other important flavor compounds, such as 2-phenylethylacetate (a high-value aromatic ester (Etschmann et al 2002) and a potential fuel molecule (Kang et al 2014), phenylacetaldehyde (flavor compound), and phydroxphenylethanol (used in pharmaceutical and fine chemical industries) (Guo et al 2017). The economic importance of 2-PE is quite significant; in 1990 it was reported that the 2-PE global market was estimated at 7000 tones, with 6000 tons used for fragrances, 10 tons for flavor applications, and 990 tons for synthesis of reaction products like esters (Etschmann et al 2002).…”
Section: Alcoholsmentioning
confidence: 99%
“…Since yeasts are good candidates for 2-PE production from L-Phe bioconversion, considerable progresses have been achieved by applying different metabolic engineering strategies of related pathways (Guo et al 2017;Kang et al 2014;Wang et al 2017). In yeasts, several genes are involved in the catabolism of L-Phe to 2-PE via Ehrlich pathway.…”
Section: Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation